OF MILITARY SERVANTS OF ENGINEERING TROOPS PEDAGOGICAL POSSIBILITY OF DEVELOPING MECHANISMS FOR IMPROVING THE QUALITY OF EDUCATION (Multidisciplinary Journal of Science and Technology, 2024)
In the article, the creation of a scientific and theoretical basis for the development of mechanisms for improving the quality of education of engineering troops can be considered as an important pedagogical task. The full performance of duties by military personnel of the engineering troops allows us to prepare professional representatives of the army, consisting of true patriots and qualified specialists in their field. The training of engineering troops in higher military educational institutions is important for the performance of such a serious, very responsible and honorable task.